Peran Teknologi Dalam Mendukung Inovasi Pendidikan Islam Di Era Globalisasi - Saprianingsih, Sri Whenti; Rahmania, Elvina; Ismail, Fajri; Afgani, Muhammad Win (Peneliti.net, 2025)
In the current era of globalization, technological developments have a significant impact on various sectors, including Islamic education. The purpose of this study is to determine the role of technology in supporting innovation in Islamic education in the era of globalization. Information and communication technology allows for major transformations in the teaching and learning process, making Islamic education more dynamic and adaptive to changes in the times. The results show that the role of technology in innovation in Islamic education covers various aspects, such as accessibility, efficiency, and wider dissemination of knowledge. One of the main roles of technology is to expand access to Islamic education. Through online platforms, religious lessons can be accessed by anyone, anytime, without being limited by distance and time. This also encourages the creation of a more interactive learning environment, where students can learn through various media, such as videos, applications, and discussion forums. Technology also facilitates digital-based learning that allows teaching Islamic materials in a more interesting and easy-to-understand way. Application-based learning provides space for students to access materials independently, in depth, and according to their needs. With the right use of technology, Islamic education can be more developed and relevant amidst the dynamics of globalization, so that it can produce a generation of Muslims who are intelligent, creative, and ready to face the challenges of the times.